2020
DOI: 10.3892/mmr.2020.11575
|View full text |Cite
|
Sign up to set email alerts
|

Role of MAPK/JNK signaling pathway on the regulation of biological behaviors of MC3T3‑E1 osteoblasts under titanium ion exposure

Abstract: The oral cavity is a complex environment that is constantly undergoing remodeling. This provides a favorable electrolytic aqueous condition, which causes the corrosion of titanium implants and the release of titanium (Ti) ions. The accumulation of Ti ions in the peri-implant tissues may affect the osteogenesis process. Therefore, the present study aimed to investigate the possible effects of Ti ions on osteoblast physiology and its underlying mechanism, specifically the MaPK/JnK signaling pathway. in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…IL-12 is not toxic itself but prompts a neutrophil response that determined the severity of tissue damage [57,58], therefore our results may suggest that sitagliptin can control excessive levels of IL-12. Studies determined the important roles of MAPK and AKT signaling pathways in peri-implantitis [59][60][61]. Our study showed that P. gingivalis LPS significantly enhanced the phosphorylation of p38 MAPK, AKT and ERK while the treatment of sitagliptin decreased the phosphorylation, suggesting that sitagliptin may exert anti-inflammatory effects by inhibiting the MAPK and AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 67%
“…IL-12 is not toxic itself but prompts a neutrophil response that determined the severity of tissue damage [57,58], therefore our results may suggest that sitagliptin can control excessive levels of IL-12. Studies determined the important roles of MAPK and AKT signaling pathways in peri-implantitis [59][60][61]. Our study showed that P. gingivalis LPS significantly enhanced the phosphorylation of p38 MAPK, AKT and ERK while the treatment of sitagliptin decreased the phosphorylation, suggesting that sitagliptin may exert anti-inflammatory effects by inhibiting the MAPK and AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 67%
“…IL-12 is not toxic itself but prompts a neutrophil response that determined the severity of tissue damage [57,58], therefore our results may suggest that sitagliptin can control excessive levels of IL-12. Studies determined the important roles of MAPK and AKT signaling pathways in peri-implantitis [59][60][61]. Our study showed that P. gingivalis LPS significantly enhanced the phosphorylation of p38 MAPK, AKT and ERK while the treatment of sitagliptin decreased the phosphorylation, suggesting that sitagliptin may exert anti-inflammatory effects by inhibiting the MAPK and AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 67%
“…The MAPK signaling cascade pathway, an important signaling pathway known to be involved in the regulation of osteoblast physiology, plays a major role in several processes, including cell proliferation, death, and differentiation [ 33 ]. This signaling pathway consists of several components, including JNK and p38 [ 34 ]. JNK signaling is broadly activated by oxidative stress and acts as a regulator for several life cycle processes, including cellular meiosis, mitosis, differentiation, and energy metabolism [ 35 ].…”
Section: Discussionmentioning
confidence: 99%